2019
DOI: 10.1037/ser0000299
|View full text |Cite
|
Sign up to set email alerts
|

Organizational trauma-informed care: Associations with individual and agency factors.

Abstract: In response to the growing awareness of the high rates of potentially traumatic experiences and their potential adverse impacts, health and human service providers have increasingly focused on implementing trauma-informed care (TIC). However, studies focusing on effective implementation have been limited. In this study, we explored the relationship of individual and agency characteristics to the level of organizational TIC. With data collected from a sample of 345 providers from 67 agencies, we used the TICOME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…A population-wide study found traumatic symptoms in frontline workers a pervasive problem in organizations that serve persons experiencing homelessness, with reported rates indicating a potential PTSD diagnosis of 33% to 36% (Authors, 2019). While the work by Authors (2019) needs validations across other geographies, it concurs with field reports of high rates of staff stress and reports by others [6,7].…”
supporting
confidence: 63%
See 2 more Smart Citations
“…A population-wide study found traumatic symptoms in frontline workers a pervasive problem in organizations that serve persons experiencing homelessness, with reported rates indicating a potential PTSD diagnosis of 33% to 36% (Authors, 2019). While the work by Authors (2019) needs validations across other geographies, it concurs with field reports of high rates of staff stress and reports by others [6,7].…”
supporting
confidence: 63%
“…plethora of work has addressed this prevalence in the general population, estimated to range from 80 % to 90% [2,3], with many people reporting multiple events. In specific client groups, such as those receiving social and child welfare services, mental health counselling and housing the incidence of trauma has been widely documented [4,5,6]. Additionally, high rates of traumatic experiences are also reported among the millions who report experiences with homelessness [4,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that after implementation of TIC, youth welfare staff in these institutions showed significantly reduced stress levels and experienced fewer client physical aggression compared to staff who did not receive training in TIC. The significant reduction after T4 indicates that training and knowledge of psycho-traumatology are not enough to change institutional practice and reduce the stress level of staff [22,66] and that such implementation processes take time and the allocation of resources [20]. It appears necessary to develop and implement TIC key procedures in those institutional processes and structures focusing on client and staff safety and self-efficacy in interactions, towards a kind of supply chain in which the management supports staff and staff support clients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high prevalence of traumatic life events in young people living in out of home placement and the need of placement continuity, some countries have realized countrywide implementation processes [17][18][19]. The challenge for youth welfare, juvenile justice, mental health institutions regarding the implementation process of TIC is that lies in the process of organization development which includes fundamental changes in attitudes and key processes and scrutinizes established institutional practice and structures [20,21]. However, overall the implementation of TIC is associated with higher staff satisfaction [22].…”
Section: Introductionmentioning
confidence: 99%